Association between Life’s Crucial 9 and overactive bladder: the mediating role of weight-adjusted-waist index - Gong, Hongyang; Duan, Shuqin; Huang, Shaoqun (Frontiers in Nutrition, 2025)
BackgroundResearch suggests a potential connection between cardiovascular health, obesity, and overactive bladder (OAB). However, the mechanisms by which obesity influences the relationship between cardiovascular health and OAB remain unclear. Life’s Crucial 9 (LC9) is a recently proposed method for assessing cardiovascular health, while the weight-adjusted waist index (WWI) is a novel and more accurate measure of obesity. This study investigates the relationship between LC9 and OAB and assesses whether WWI moderates this relationship.MethodsData for this study came from the National Health and Nutrition Examination Survey (NHANES). We used subgroup analyses, restricted cubic spline curves (RCS), and multivariate logistic regression to explore the relationship between LC9 and OAB. Additionally, mediation analysis was conducted to investigate the potential association between WWI levels and the relationship between LC9 and OAB.ResultsA total of 25,319 participants were included in this study, among which 5,038 reported incidents of OAB. After adjusting for all variables using multivariable logistic regression, an increase of 10 units in LC9 was associated with a 28% reduction in the incidence of OAB (OR = 0.72, 95% CI: 0.69, 0.76), while an increase of one unit in WWI was associated with a 40% increase in the incidence of OAB (OR = 1.40, 95% CI: 1.29, 1.51). Consistent results were also observed when LC9 and WWI were categorized into quartiles, with a P for trend <0.001. The analysis using restricted cubic splines indicated a linear negative correlation between the incidence of OAB and LC9. Mediation analysis revealed that 13.89% of the relationship between LC9 and OAB was mediated by WWI (p = 0.002).ConclusionThis study found a significant negative correlation between LC9 and OAB, with WWI acting as a partial mediator in this relationship. This study provides new insights for future research into the relationship between LC9 and OAB and the role of WWI as a mediator.